Mapping collaboration and impact of library and information science research in sub-Saharan Africa, from 1995 to 2016. Issue 6 (13th August 2018) - Onyancha, Omwoyo Bosire
Abstract : Purpose: The purpose of this paper is to map and visualise collaboration patterns and citation impact of the library and information science research in sub-Saharan Africa between 1995 and 2016. Design/methodology/approach: Data were extracted from the Thomson Reuters' citation indexes using the name of the country in an advanced search platform. The search was limited to documents designated as articles. Data were analysed using the VosViewer software to obtain network maps and frequencies of occurrence. Findings: The findings reveal that publication and citation impact of LIS research in sub-Saharan Africa has continued to grow since 1995; foreign countries have immensely contributed to the evolution and development of LIS research in the region; research collaboration occurs both regionally and internationally, with the latter being the most prominent; South Africa, Nigeria and Kenya are the most active participants in LIS research collaboration in the region; and that on average, international collaboration in LIS research in sub-Saharan Africa attracts more citations than other types of collaboration. Research limitations/implications: The study was limited to the data indexed in the Web of Science citation indexes and focused on sub-Saharan African countries only. Practical implications: Collaboration is said to lead to increased research output and impact, hence the need for sub-Saharan African researchers and institutions to initiate strategies that will create conducive environments for research collaboration. There is need for collaborative ventures between LIS practitioners and educators as well as increased cooperation among LIS schools within and outside of sub-Saharan African countries. Partnerships involving students and programmes such as research fellowship, post-doctoral researchers as well as visiting researchers may complement any existing strategies that can be pursued to increase collaborative research in LIS in the region. Originality/value: The paper, while drawing lessons from previous papers, adopted a variety of techniques to examine collaboration patterns and impact of LIS research over a longer period of publication time, i.e. 1995 to 2016, and a larger geographic scope.